1977
DOI: 10.2307/2094604
|View full text |Cite
|
Sign up to set email alerts
|

Insurgency of the Powerless: Farm Worker Movements (1946-1972)

Abstract: Drawing on the perspective developed in recent work by Oberschall (1973), Tilly (1975) and Gamson (1975), we analyze the political process centered around farm worker insurgencies. Comparing the experience of two challenges, we argue that the factors favored in the classical social movement literature fail to account for either the rise or outcome of insurgency. Instead, the important variables pertain to social resources-in our case, sponsorship by established organizations. Farm workers themselves are powerl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
266
0
17

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 706 publications
(288 citation statements)
references
References 11 publications
5
266
0
17
Order By: Relevance
“…For example, social movement theories based in the US and Europe, including the political process model (Tarrow 1994;McAdam 1999;McAdam, Tilly, and Tarrow 2001), the resource mobilization approach (Jenkins and Perrow 1977;McCarthy and Zald 1977;Tilly 1978) and discussions of 'repertoires' of contention (Tilly 2008), are primarily focused on movement emergence and mobilization over time. In the political process perspective, social movements are defined as 'rational attempts by excluded groups to mobilize sufficient political leverage to advance collective interests through non-institutionalized means' (McAdam 1999, 37).…”
Section: Social Movements the State And Dominant Economic Interestsmentioning
confidence: 99%
“…For example, social movement theories based in the US and Europe, including the political process model (Tarrow 1994;McAdam 1999;McAdam, Tilly, and Tarrow 2001), the resource mobilization approach (Jenkins and Perrow 1977;McCarthy and Zald 1977;Tilly 1978) and discussions of 'repertoires' of contention (Tilly 2008), are primarily focused on movement emergence and mobilization over time. In the political process perspective, social movements are defined as 'rational attempts by excluded groups to mobilize sufficient political leverage to advance collective interests through non-institutionalized means' (McAdam 1999, 37).…”
Section: Social Movements the State And Dominant Economic Interestsmentioning
confidence: 99%
“…Successful insurgencies typically do not emerge merely because of widespread political instability, but also because of broad social processes that have strengthened the aggrieved population's political power. 40 'Consequently, the increase in political opportunity through enhanced political positions for movement groups is usually achieved more gradually than through political instability.' 41 Finally, broad social changes can lead the social environment to tolerate alternative, critical and even subversive ideas and world-views espoused by the aggrieved population and other associated movements.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…For example, in their study of farm worker movements in the United States, Jenkins and Perrow (1977) concluded that increased outside support (both symbolic and concrete) due to changes in the political process, rather than changes in the level of discontent, were most important for the growth of the United Farm Workers movement in the 1960s. Jenkins and Perrow's data tend to support this argument, with one significant weakness; they assumed a consistent level of deprivation among farm labor.…”
Section: Participants (Hirsch 1990) In Part This Psychological Aspementioning
confidence: 99%